Optimum dietary protein requirement of Malaysian mahseer (Tor tambroides) fingerlings. - Dorin, Josephine; Kamarudin, Mohd. Salleh; Musa, Mazlinda (Asian Network for Scientific Information, 2011)
The optimum dietary protein requirement of the Malaysian mahseer (Tor tambroides) fingerlings was determined in this study. In this completely randomized designed experiment, formulated diets of five levels of dietary protein (30, 35, 40, 45 and 50%) were tested on the T. tambroides fingerlings (initial body weight of 5.85 +/- 0.40 g), reared in aquarium fitted with a biofiltering system. The fingerlings were fed twice daily at 5% of biomass. The fingerling body weight and total length was taken at every two weeks. Mortality was recorded daily. The dietary protein had significant effects on the body weight gain and Specific Growth Rate (SGR) of the fingerlings. The body weight gain and SGR of fingerlings fed with the diet with the dietary protein level of 40% was significantly higher (p<0.05) than that of 30, 35 and 50%. The feed conversion ratio of the 40% dietary protein was the significantly lowest at 2.19 +/- 0.163. The dietary protein level of 40% was the most optimum for T. tambroides fingerlings.